Definition of the components required for selective packaging of coronavirus genomic RNA - Janice D. Pata; Taína K. Stevens; Lili Kuo; Paul S. Masters (Proceedings of the National Academy of Sciences, 2025)
Most cytoplasmic RNA viruses have evolved mechanisms to identify their genomic RNA (gRNA) as the sole RNA species to be packaged into assembled virions. Coronaviruses exhibit highly selective packaging of their gRNA, in spite of the presence of a large excess of subgenomic viral and host RNA in infected cells. Failure to accomplish this selectivity does not impair virion assembly but renders the virus vulnerable to host innate immunity. In the prototype coronavirus mouse hepatitis virus (MHV) packaging selectivity is brought about by a packaging signal (PS), an RNA structure found exclusively in gRNA and absent from subgenomic RNAs. However, it is not well resolved how virion structural proteins participate in the recognition of the PS. Previous studies with virions have shown that the nucleocapsid (N) protein carboxy-terminal RNA-binding domain (CTD) and the carboxy-terminal tail (domain N3) both have roles in PS recognition. Separately, work with a virus-like particle system has implicated the viral membrane (M) protein as the main factor in this process. Here, we pinpoint key amino acids in the CTD and domain N3 that govern selective gRNA packaging into virions, and we provide genetic evidence that the M protein endodomain also plays a required role. We show that the N protein CTD is the primary determinant of PS recognition, and we localize residues in the CTD structure that are critical for specific and nonspecific RNA binding.